ChemInform Abstract: Synthesis, Characterization, Biological Evaluation and QSAR Studies of 11‐p‐Substituted Phenyl‐12‐phenyl‐11a, 12‐dihydro‐11H‐indeno[2, 1‐c][1, 5]benzothiazepines as Potential Antimicrobial Agents. Issue 16 (28th March 2013) - Mor, Satbir; Pahal, Preeti; Narasimhan, Balasubramanian
Abstract The condensation reaction of (E)‐benzylideneindanones (I) with o‐aminobenzenethiols (II) proceeds diastereoselectively to furnish novel title benzothiazepine derivatives (III) (16 examples) as single diastereoisomers.